CUSTOMER RELATIONSHIP MANAGEMENT (CRM) SEBAGAI STRATEGI DALAM MENJAGA LOYALITAS PELANGGAN: CUSTOMER RELATIONSHIP MANAGEMENT (CRM) SEBAGAI STRATEGI DALAM MENJAGA LOYALITAS PELANGGAN - febrina, poppy; Lestari, Serli (Majalah Ilmiah Manajemen STIE Aprin Palembang, 2023)
This research aims to examine the concepts of Customer Relationship Management (CRM) which include definitions, objectives, benefits, and the important role of Customer Relationship Management (CRM) in maintaining customer loyalty. This research uses a literature review approach which is expected to be one of the references for customers so that it can be used in the future. Customer Relationship Management (CRM) not only serves to keep customers from moving from one company / product to another, but at the same time it is one of the strategies in getting potential customers, this is because previous customer satisfaction moves to other potential customers, one of which is through WOM (Word Of Mouth). When Customer Relationship Management (CRM) is successfully implemented, it will create customers who are loyal to the company and give a good impression of the company.